FEATURES OF GEOLOGICAL STRUCTURE AND PROSPECTS OF OIL-AND-GAS BEARING CAPACITY OF THE RIPHEAN AND VENDIAN DEPOSITS IN THE SOUTHEASTERN PART OF THE KAMO ARCH OF THE BAYKIT ANTICLISE - V. A. Fomin; A. G. Vakhromeev; Z. L. Motova; A. V. Strunov; D. V. Mashenkin; V. V. Fomina; A. V. Plusnin (Геодинамика и тектонофизика, 2024)
The paper presents the results of the integrated study of the features of geological structure of the southeastern Kamo arch of the Baikit anticlise. Use has been made of both already published and unpublished geological-geophysical data obtained through seismic survey using the common depth point (CDP 2D) and the side view seismic location (SVSL) methods. The conducted research made it possible to improve understanding of the geological structure and formation conditions of the terrigenous-carbonate rocks of the Lower Riphean (Madrа, Yurubchen and Dolgokit formations) and Vendian (Vanavara and Oskoba formations) Kamo Group in the southern Kamo arch of the Baykit anticlese in terms of the prospects for the discovery of hydrocarbon (HC) deposits therein. The interpretation of seismic data (CDP and SVSL) provided the possibility to specify the thickness of the Lower Riphean terrigenous-carbonate rocks, most promising for hydrocarbons, to generate the predictive geology map of the pre-Vendian erosion surface, and to map the HC-promising Early Riphean and Vendian deposit thickness. Along with the previously explored large HC deposits in the central Kamo arch of the Baykit anticlise, the new data presented here testify in favor of the structural-and tectonic conditions for the development of the Lower Riphean and Vendian rocks on the southeastern slope of the Kamo arch of the Baykit anticlise and imply their high potential.